Dynamic Tests of Pony Truss Railway Bridge Under Normal Operation - PRADELOK Stefan; POPRAWA Grzegorz (Architecture, Civil Engineering, Environment)
The article describes the application of dynamic tests during normal operation in assessing the technical condition of the railway bridge on the Nysa Łużycka River. The investigated structure consists of six steel pony truss spans. Operational modal analysis was used to identify dynamic parameters. The results obtained were applied to verify the numerical model used in the assessment process of technical condition and in determining the current load capacity of the structure created in the 1950s. The experiment conducted allowed us to observe the dynamic response of the pony-truss bridges. The study demonstrated that dynamic tests during normal operation and the use of other available environmental excitations could complement other non-destructive diagnostic methods. This proves that we can obtain useful information about the dynamic properties of a structure without closing the traffic and without the application of the ordinary dynamic test load.